Návrh modelu produkce pro restauraci - Bazhin, Ivan (Vysoké učení technické v Brně. Fakulta podnikatelská, 2023)
Bakalářská práce se zaměřuje na modelování produkčního systému z hlediska matematických a statistických metod. V této práci autor podrobně zkoumá problematiku výrobních procesů v restauraci a klade důraz na zásobování, nákup a předběžné přípravy pokrmů. Základem výsledného modelu je statistické předpovídání poptávky po vybraných jídlech.

The bachelor thesis focuses on the modelling of the production system in terms of mathematical and statistical methods. In this thesis, the author examines in detail the issues of production processes in a restaurant and emphasizes on supply, purchasing and pre-preparation of food. The basis of the resulting model is statistical forecasting of demand for selected meals.
Production Model for a Restaurant
Keywords: Regresní analýza; model produkce; poptávka; restaurace; statistika; výrobní proces; zásobovaní; informační managment.; Regression analysis; production model; demand; restaurant; statistics; production process; supply; information management.